"Who needs an app? Fertility patients' use of a novel mobile health app". (May 2022) - Miner, Skye A; Gelgoot, Eden N; Lahuec, Alix; Wunderlich, Samantha; Safo, Darryl; Brochu, Felicia; Dawadi, Shrinkhala; Robins, Stephanie; Bernadette, Siobhan; O'Connell, Laura; Chan, Peter; Ells, Carolyn; et al.
Objective: The number of couples experiencing infertility treatment has increased, as has the number of women and men experiencing infertility treatment-related stress and anxiety. Therefore, there is a need to provide information and support to both men and women facing fertility concerns. To achieve this goal, we designed a mhealth app, Infotility, that provided men and women with tailored medical, psychosocial, lifestyle, and legal information. Methods: This study specifically examined how fertility factors (e.g. time in infertility treatment, parity), socio-demographic characteristics (e.g. gender, education, immigrant status), and mental health characteristics (e.g. stress, depression, anxiety, fertility-related quality of life) were related to male and female fertility patients' patterns of use of the Infotility app. Results: Overall, the lifestyle section of the app was the most highly used section by both men and women. In addition, women without children and highly educated women were more likely to use Infotility. No demographic, mental health or fertility characteristics were significantly associated with app use for men. Conclusion: This study shows the feasibility of a mhealth app to address the psychosocial and informational needs of fertility patients.